Electrochemical and spectroelectrochemical characterizations of phthalocyanines bearing peripherally tetra-4-carboxyethylenephenoxy anchoring groups and usage as photosensitizers of dye-sensitized solar cell - KOCA, ATIF (My University, 2023)
© 2022 Elsevier B.V.A series of metal-free and metallo phthalocyanines (MPc) peripherally substituted with tetra-4-carboxyethylenephenoxy (M = 2H+ (H2Pc), Co2+ (CoPc), Zn2+ (ZnPc), and TiO2+ (TiOPc)) are used as dyes in the dye-sensitized solar cells (DSSCs). To predict the feasibility of MPcs as photosensitizers, electrochemical and in-situ spectroelectrochemical characterizations are first carried out since their redox mechanisms and optical responses under electrochemical excitations are the key factor for the requirement of the photosensitizers in DSSCs. The redox activities and opto-electrochemical responses of the compounds make them promising dye candidates with electrochemically reversible and multi-electron electron transfer reactions and suitable HOMO-LUMO band positions. The DSSCs using TiO2 film modified with these MPcs are developed and characterized. DSSC analyses indicate that especially H2Pc and TiOPc among the MPcs illustrate better photovoltaic performances than the others. The increase in efficiency of DSSC consisting of H2Pc and TiOPc is mainly associated with their suitable band positions and high electron lifetimes. When compared with the Pc bearing various substituents, ethylenephenoxy linkers between the Pc ring and the carboxyl anchoring groups significantly enhance the push-pull features between the dyes and TiO2 semiconductor, which results in 1.15, 2.98, 3.17 and 3.97 % power conversion efficiencies with CoPc, ZnPc, H2Pc, and TiOPc based DSSCs respectively.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Analitik Kimya; Fizikokimya; Elektrokimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Analytical Chemistry; Physical Chemistry; Electrochemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, KİMYASAL; KİMYA, ANALİTİK; ELEKTROKİMYA; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; ENGINEERING, CHEMICAL; CHEMISTRY, ANALYTICAL; ELECTROCHEMISTRY; Fizik Bilimleri; Genel Kimya Mühendisliği; Physical Sciences; General Chemical Engineering; Carboxyethylenephenoxy substituents; Dye-sensitized solar cell; Phthalocyanine; Spectroelectrochemistry